CHARACTERISTICS OF WORKPLACE AGGRESSION IN MEDICAL PRACTICE - Stanislava Pavlova; Ivelina Dyankova (Peytchinski Publishing, 2024)
Purpose: To study and analyze the presence of aggression in the workplace among medical professionals in emergency departments. Material/Methods: The study included 227 medical and non-medical personnel from emergency units in the Varna region. Documentary, sociological, and statistical methods are applied. The study was carried out in 2023. Results: A large proportion of emergency workers were the object of aggression from patients or their relatives during work (84.1%, n=191). The object of aggression is the employees in the age group of 51-65 years (35.2%, n=80). More often, aggression is verbal aggression. Doctors and nurses are the object of aggression more often than other categories of staff. Aggression leads to a decrease in the pace of work, intention to leave the workplace, etc. Negative emotional reactions to the intake of alcohol or narcotic substances are among the reasons leading to aggression of the patient or his relatives. Conclusion: The professional activity of medical specialists is related to mental and physical stress. Violence in the workplace is a prerequisite for stress and anxiety. It adversely affects workers.